Low Temperature Preparation of KNbO3Films by Hydrothermal Method and Their Characterization. Issue 1659 (2014) - Kaneko, N.; Shiraishi, T.; Kurosawa, M.; Shimizu, T.; Funakubo, H.
ABSTRACT: KNbO3 films were prepared at 100 - 240°C on (100)c SrRuO3 //(100)SrTiO3 substrates by hydrothermal method using KOH and Nb2 O5 as source materials. The incubation time before starting deposition and the deposition rate after starting deposition increased and decreased with decreasing deposition temperature, respectively. Epitaxial 100 c -oriented KNbO3 films with 300 nm thick were successfully obtained at 100°C on (100)c SrRuO3 //(100)SrTiO3 substrates for 144 h. We observed the typical butterfly-shape strain curves originated from the piezoelectricity for the first time for KNbO3 films deposited down to 120°C.